Kesetimbangan Adsorpsi Zat Pewarna Rhodamine-B Menggunakan Fly Ash Sawit Sebagai Low-Cost Adsorbent - Olsy, Fradilla; Saputra, Edy; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Rhodamine B is one of the various toxic dye that contributes significantly to environmental pollution, because it is non-biodegradable, toxic and harmful to the environment. One effort to reduce the amount of rhodamine b is the adsorption process. One of the good adsorbent that can be use for adsorbtion process is palm oil fly ash. The purpose of this study to aim the effect of adsorption temperature, pH, and adsorbent mass. Knowing the optimum conditions for reducing the levels of dye in the water, as well as determine the adsorption equilibrium models rhodamine b using fly ash oil modified with 0,1M HCl as an adsorbent. Fly ash modification processes are done by mixing fly ash and HCl in the ratio 1:10 of 0,M HCl solution. The adsorption process is conducted by mixing fly ash 0.5; 1; 1,5 and 2g/L and pH solution of rhodamine b 2; 4; 6; 8 with temperature of 30; 35; 45oC and with various of rhodamine b’s initial solution 10, 20, 30 dan 40ppm. The optimum conditions for reducing the levels of rhodamine B in water is the adsorbent mass of 2g/L, temperature of 45°C and pH 8 at 10ppm concentration rhodamnine’s solution. Thermodynamic data such as ΔH, ΔG and ΔS were calculated. And the mechanism of rhodamine B dye adsorption by fly ash oil is suit well with Freundlich and Langmuir isotherm models.Keyword: Adsorption, Isothermal Adsorption, Palm Oil Fly ash, Rhodamine B,